Plant growth promoter collection of Gluconacetobacter diazotrophicus from northern coast of Peru - Paredes-Villanueva, Johnnel (2020)
The application of plant growth promoting bacteria (PGPB) represents a friendly alternative to the environment, in contrast to the use of chemical fertilizers. Endophytic bacteria can develop inside the plant tissues and directly benefit the plant. Gluconacetobacter diazotrophicus is a versatile bacterium that has been isolated from different plants and possesses different physiological properties that would serve to improve plant development. In this research, five cultures of G. diazotrophicus were isolated from sugarcane samples from the northern coast of Peru. The isolates showed the ability to solubilize phosphates and zinc, produce IAA, and resist salt stress (NaCl 1%). Antagonism evaluations showed that they can inhibit up to 75%, 57%, 40%, 49% and 17% of the development of Fusarium sp., Alternaria sp., Roselinia sp., Lasiodiplodia sp., and Sclerotinia sp., respectively. Inoculation plant experiments were developed by inoculating individual and bacteria mixture. All treatments showed plant growth promotion in sugarcane, but mixture of G. diazotrophicus LASFB 1573, Klebsiella sp. LASFBP 086 and Enterobacter sp. LASFB 009 increased up to 84% and 89% in fresh and dry plant weight, respectively. The results show that the isolates have a high potential as PGPB and could be used later to improve the development of different crops.